Access to Information and Adoption of New Farming Practices: A Spatial Analysis - Shobhit Kulshreshtha (Global Labor Organization (GLO), 2024)
In this study, I delve into the factors shaping the adoption of new farming practices among Indian farmers, with a particular focus on the role of information access and its diverse sources. Leveraging nationally representative data on rural households from the National Sample Survey Office, Government of India for the year 2019, I employ logistic regression to gauge the likelihood of farmers adopting new agricultural techniques based on the information they receive from various channels. Additionally, I undertake spatial linear regression analysis to unravel the dynamics of information spillovers pertaining to new farming practices across districts. The results highlight the significance of the information source in driving adoption decisions, with progressive farmers and input dealers emerging as influential sources. Moreover, the spatial analysis provides compelling evidence of information diffusion across district boundaries, highlighting the varying efficacy of different information channels. These findings offer valuable insights for policymakers aiming to craft targeted interventions aimed at shaping farmers' decision-making processes regarding the adoption of innovative farming practices.
Keywords: Q15; Q16; Q54; 330; Farming Practices; Information Access; Technology Adoption; Spatial Spillovers